Tingkat Prevalensi Toksoplasmosis Pada Kucing Peliharaan Di Enam Kecamatan Di Kota Kupang - Wuri, Diana A; Kallau, Novalino H.G; Scriptiantino Haan, Vivaldi Abraham (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Cats are one of the most popular animals among the people,their popularity makes the number of cat enthusiasts inIndonesia very large, but even though cats are very popular aspets, it is not supported by sufficient knowledge about good andcorrect way in the maintenance pattern of cats. Poormaintenance patterns can cause several diseases, which canattack both cats and humans, like toxoplasmosis infection.Toxoplasmosis is an infectious disease caused by the protozoaToxoplasma gondii, and cats around the world are a latentsource of T.gondii infection. The purpose of this study was todetermine the prevalence and distribution of toxoplasmosis inpet cats in Kupang City. In this study, samples of pet cat faeceswere taken from six subdistricts in Kupang City with a totalsample of 81 faecal samples. The collected samples were thenexamined using the flotation method. From the results of thestudy, the number of positive samples was 19 samples, with aprevalence of 23%. If you look at the distribution map,toxoplasmosis in pet casts has spread evenly with the number ofpositive samples in each subdistrict is not much different.